Design and implementation of a security communication system for a local area: case study the university of bamenda - Suh Charles Forbacha; Walters Marlene Bih Mbakwa Anagho (Research Parks Publishers, 2021)
The expensive, inefficient and unreliable nature of the existing communication systems, makes them inadequate for use in raising security awareness in local areas such as the University of Bamenda campus. With the current sociopolitical crisis in the region, there is a need for a reliable communication system which can be used to improve upon the security of staff and students on campus. This research project proposes a solution which is cost, time and power efficient. This system was analyzed and designed by following an evolutionary prototyping life cycle model which consists of developing a robust prototype in a structured manner which is constantly refined with user feedback to get a better end product. Mathematical analysis of the system components was used to determine the system specifications for the project. This solution has a low power requirement and does not depend on mobile networks. Simulation results showed our system is capable of receiving and transmitting information without any degradation of the signal within a 100m range when supplied with a 9V dc supply.